Determinants of Indonesia’s Food Security 2019–2023: A Panel Data Analysis - Christy Celistia Daulay; Sudarsana Arka (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
Food security is a critical pillar for ensuring socio-economic stability and achieving sustainable development. This study analyzes the influence of rice production, gross regional domestic product (GRDP) per capita, poverty rate, access to clean water, and the COVID-19 pandemic on Indonesia's food security during the 2019–2023 period. Using panel data regression with the Random Effects Model (REM), the results indicate that rice production, poverty, and access to clean water significantly affect food security. Interestingly, the COVID-19 dummy variable shows a significant positive effect (2020–2022), indicating improved food security during the pandemic years. These findings highlight the effectiveness of government responses, particularly through social protection and food distribution programs. The study provides insights for future policies that prioritize increasing domestic food production, poverty alleviation, and equitable access to clean water as strategies to strengthen sustainable food security.